TEL/AML1 positivity in childhood ALL: average or better prognosis? Czech Paediatric Haematology Working Group - Zuna, J; Hrusák, O; Kalinová, M; Muzíková, K; Starý, J; Trka, J (Leukemia, 1999)
The presence of TEL/AML1 fusion gene in childhood acute lymphoblastic leukaemia (ALL) defines a subgroup of patients with better than average outcome. However, the prognostic significance of this aberration has recently been disputed by the Berlin-Frankfurt-Münster (BFM) study group due to its relatively high incidence found in relapsed patients (19.6% and 21.9%, in two cohorts). In contrast, only four out of 45 (8.9%) unselected relapsed patients (all of whom had been treated according to BFM protocols) in the Czech Republic carry this fusion. From March 1995 to June 1998, 41 out of 190 (21.6%) newly diagnosed children with ALL were TEL/AML1-positive. There is a statistically significant difference between the incidence of TEL/AML1 fusion at diagnosis and at relapse within our group (P = 0.035). Interim analysis of the minimal residual disease (MRD) detection shows heterogeneity within the group of newly diagnosed TEL/AML1-positive leukaemias--10 out of 24 patients tested at the end of induction therapy had detectable levels of MRD. However, only one of these patients reached relapse-predictive level (10(-3)) of MRD. In conclusion, we corroborate low frequency of TEL/AML1 positivity among relapsed patients with ALL among Czech children who are treated by the BFM protocols. Moreover, we demonstrate different patterns of bone marrow clean-up in TEL/AML1-positive patients.
Keywords: recidiva; exony; Bone Marrow; nádorové proteiny; Humans; translokace genetická; počet leukocytů; dítě; Child; fúzní onkogenní proteiny; Exons; Translocation, Genetic; lidé; Leukocyte Count; Oncogene Proteins, Fusion; Core Binding Factor Alpha 2 Subunit; Adolescent; prognóza; kostní dřeň; Czech Republic; Gene Rearrangement; Recurrence; akutní lymfatická leukemie; genová přestavba; protein PEBP2A2; Česká republika; Neoplasm Proteins; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Prognosis; mladiství